2022
DOI: 10.1002/fft2.167
|View full text |Cite
|
Sign up to set email alerts
|

Edible insects: A novel nutritious, functional, and safe food alternative

Abstract: In a world where 1 billion people suffer from hunger, lands and seas are overexploited and production systems are unsustainable, and there is an urgent need to find alternative foods. In this context, insects represent a good source of macro-and micronutrients and even bioactive compounds that could contribute to reducing nutritional deficiency and preventing some human diseases. However, some aspects related to their consumption, including health risks, need to be clarified. This communication aims to summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…3 In their dried forms, most of the species contain high quantities of proteins, unsaturated fatty acids, vitamins, minerals, and fibre, which makes them a suitable component for human consumption. [4][5][6] These edible insects can be treated to yield ingredients like protein isolates or concentrates. Following that, enzymatic hydrolysis and fermentation can be employed to manufacture protein hydrolysates, which can include peptides with potential physiologically relevant effects, and would be considered bioactive peptides.…”
Section: Edible Insects As a Source Of Proteinmentioning
confidence: 99%
“…3 In their dried forms, most of the species contain high quantities of proteins, unsaturated fatty acids, vitamins, minerals, and fibre, which makes them a suitable component for human consumption. [4][5][6] These edible insects can be treated to yield ingredients like protein isolates or concentrates. Following that, enzymatic hydrolysis and fermentation can be employed to manufacture protein hydrolysates, which can include peptides with potential physiologically relevant effects, and would be considered bioactive peptides.…”
Section: Edible Insects As a Source Of Proteinmentioning
confidence: 99%
“…Studies have demonstrated that the bioactivity and health benefits for human of T. molitor , G. bimaculatus , and G. sigillatus have been well illustrated and investigated (Pyo et al., 2020; Dong et al., 2021; Ordoñez‐Araque & Egas‐Montenegro, 2021; Hierro et al., 2022; Kemsawasd et al., 2022). Furthermore, adding house cricket powder to meat and bakery products has been explored to enhance their nutritional value, texture, and foam ability (Xavier et al., 2020; Borges et al., 2022; Giampieri et al., 2022). However, there is still a lack of research on the potential health benefits associated with the consumption of A. domesticus .…”
Section: Nutraceutical and Pharmaceutical Properties Of A Domesticus ...mentioning
confidence: 99%
“…These can accumulate in the body of insects throughout their life due to different factors such as species, developmental stage, and feed substrate. The presence of arsenic and cadmium has been found in yellow mealworm larvae, Bombay locust, scarab beetle, black soldier flies, house cricket, and mulberry silkworm [ 57 ].…”
Section: Possible Risks To Be Taken Into Account When Consuming Insectsmentioning
confidence: 99%